Neuromodulation, Emotional Feelings and Affective Disorders - Wang, Fushun; Pereira, Alfredo [UNESP] (Wolters Kluwer, 2016)
Affective disorders such as anxiety, phobia and depression are a leading cause of disabilities worldwide. Monoamine neuromodulators are used to treat most of them, with variable degrees of efficacy. Here, we review and interpret experimental findings about the relation of neuromodulation and emotional feelings, in pursuit of two goals: (a) to improve the conceptualisation of affective/emotional states, and (b) to develop a descriptive model of basic emotional feelings related to the actions of neuromodulators. In this model, we hypothesize that specific neuromodulators are effective for basic emotions. The model can be helpful for mental health professionals to better understand the affective dynamics of persons and the actions of neuromodulators - and respective psychoactive drugs - on this dynamics.
Keywords: Affective Disorders; Emotions; Feelings; Monoamines; Neuromodulators